Current status of various neurovascular bundle-sparing techniques in robot-assisted radical prostatectomy. Issue 3 (September 2016) - Kumar, Anup; Tandon, Sarvesh; Samavedi, Srinivas; Mouraviev, Vladimir; Bates, Anthony; Patel, Vipul
Abstract Nerve-sparing procedures during robot-assisted radical prostatectomy (RARP) have demonstrated improved postoperative functional outcomes. This article provides an overview of clinically applied prostatic neuro-anatomy, various techniques of nerve sparing (NS), and recent innovations in NS and potency outcomes of NS RARP. We retrieved and reviewed all listed publications within PubMed using keywords: nerve sparing, robotic radical prostatectomy, prostate cancer, outcomes, pelvic neuroanatomy and potency. Studies reporting potency outcomes of NS RARP (comparative and non-comparative) were analysed using the Delphi method with an expert panel of urological robotic surgeons. Herein, we outline the published techniques of NS during RARP. Potency and continence outcomes of individual series are discussed in light of the evidence provided by case series and published trials. The potency outcomes of various comparative and non-comparative series of NS RARP have also been mentioned. There are numerous NS techniques reported for RARP. Each method is complimented with benefits and constrained by idiosyncratic caveats, and thus, careful patient selection, a wise intraoperative clinical judgment and tailored approach for each patient is required, when decision for nerve sparing is made. Further large prospective multi-institutional randomized controlled trials are required to evaluate potency and continence outcomes of these techniques, using a rigid standard patient selection criteria and definition of potency are warranted in the new era of functional outcome-driven research.